Max Lamb : Exercises in Seating /. ([S.l.] : Dent-de-Leone, 2017)
For his graduate show at the Royal College of Art in 2006. Max presented seven different seats, each made in a different material and following a different production process. The title, Exercises in Seating suggested something ongoing, an evolving body of work rather than a conclusion - a learning process, where he is willing to fail. He admits that not every experiment since has gone exactly to plan: not every chair is comfortable, wax melts, hands get cut, fires start, people don't always like the end result, but each project has inspired a future exploration. Almost a decade later, the porcess continues with this book - seven chairs are now forty; like the furniture equivalent of natural selection, they are the ones that made it.
boek
Keywords: Lamb, Max